Role of the potassium channels in vasorelaxant effect of asafoetida essential oil - Hassan Esmaeili; Mansour Esmailidehaj; Somayeh Entezari Zarch; Hossein Azizian (Mashhad University of Medical Sciences, 2020)
Objective: In a previous work, we showed that asafoetida essential oil (AEO), from oleo-gum resin of Ferula asafoetida L. from the Apiaceae family, has a vasodilatory effect. This effect was both endothelium-dependent and endothelium-independent. The present study was designed to determine whether potassium channels and intracellular calcium release contribute to AEO-induced vasodilation. Materials and Methods: Rats' thoracic aorta were isolated and denuded. Following induction of contraction by potassium chloride (60 mM), concentration-response curve was plotted by the cumulative addition of AEO (0.625-80 µl/l to the medium of rings. The vasodilatory effect of AEO was assessed before and after addition of phenylephrine and potassium channel blockers (including barium chloride (BC), 4-aminopyridine (4A) and glibenclamide (Gl)). Results: AEO relaxed the precontracted rings in a concentration-dependent manner (IC50=23 µl/l). All potassium channel blockers significantly attenuated the vasodilatory activity of AEO when they were added to rings medium before addition of KCl (p<0.01, 4A and Gl groups and p< 0.001, BC group vs. control group) but not after that. In contrast to K channel blockers, adding AEO before or after phenylephrine, the tension was reduced significantly (p Conclusion: The findings of this study indicated that the vasodilatory effect of AEO on denuded-endothelium aortic ring was mediated through activation of potassium channels and reduced intracellular calcium release.